A De Lege Ferenda Perspective on Artificial Intelligence Systems Designated as Inventors in the European Patent System. Issue 2 (14th January 2021) - Stierle, Martin
Abstract: The European patent system was designed around a paradigm of human inventorship. This paper will analyse in depth and from a de lege ferenda perspective the rather general arguments against and in favour of a possible designation of artificial intelligence (AI) systems as inventors. For the sake of a more concrete discussion, it will also outline a potential reform of the European patent system to implement AI inventorship and allocate the right to the European patent for such inventions by default to the machine's operator. In the process, it will highlight the major specific issues associated with a reform that acknowledges AI inventorship and touch upon possible alternative approaches to addressing the growing autonomy of machines within the R&D process. The study must not be understood as a call for a reform to recognise AI systems as inventors but rather as a manner of laying the foundations for a more concrete, critical and fruitful discussion on non-human inventorship and its alternatives. The analysis will show that the more general, highly conceptional reservations advanced in the current discussion against AI inventorship are somewhat unfounded, e.g. the alleged break with the functions of the current patent system or the alleged need to endow AI with legal personality. More convincing arguments against a reform that allows for the designation of AI systems as inventor might instead relate to the specific difficulties associated with such reform.